Using RSA Digital Signature to Solve Pollution Problem in Single-Source Network Coding - Rami S. Youail (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Pollution problem in network coding becomes a serious problem, where no receiver can be reached by a source it does not need, in other words, the intermediate nodes may send polluted or faked messages into the network. This injection will prevent the sinks nodes from recovering the original messages correctly. Additionally, a malicious node can inject garbage into the distribution network, if undetected; the garbage will pollute the whole network. The most difficult problem in pollution propagation is the expansion of pollution. If a small number of polluted packets/messages is not detected at the early stages of the network; these small polluted messages will be expanded and used by downstream nodes and will affect the entire network. Therefore, the polluted or forged messages should be detected and filtered as early as possible before it grows up and distributed overall the network. To overcome this problem, a signature-based authentication system is proposed, which can detect the polluted or forged message at each intermediate/sink node. The system only needs to transmit the private key of the source node to each intermediate node.